Dignity Conserving Therapy: An Intervention for Addressing Psychosocial and Existential Distress in Patients with Serious Illness - Jessica Weng; Deirdre R. Pachman; Ellen Wild; Cory J. Ingram (Palliative Medicine Reports, 2022)
Patients with serious illnesses may experience existential and psychosocial distress contributing to their pain and suffering. Addressing existential distress is challenging and may require a multidisciplinary approach. Often, providers feel uncomfortable or ill equipped to care for patients suffering from this distress. In the sample case, the patient has a life-limiting disease and is concerned about his family forgetting him, experiencing loss of dignity and narrative foreclosure. Loss of dignity is sensing hopelessness and worthlessness and a loss of self-determination. Narrative foreclosure is the premature conviction that one's life story has effectively ended. Beneficial interventions include meaning-centered psychotherapy and dignity therapy (DT). Both have an underlying theme of attempting to reverse the narrative foreclosure for patients with serious illnesses and maintain a sense of meaning in life. In addition, patients can be referred to palliative care to enhance coping and decrease depressive symptoms. Dr. Harvey Chochinov has outlined a framework that clinicians can use to care for their patients in a compassionate manner to specifically combat meaninglessness. In DT, a generativity document is created for the patient and their loved ones as part of the treatment along with the opportunity to answer the dignity conserving question. Success of this route of intervention includes greater will to live, reductions in stress, and benefits perceived by family. This article aims to give a framework to treat patients with serious illnesses experiencing psychosocial and/or existential distress.